PENGARUH EARNING PER SHARE, DEVIDEN PER SHARE DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2020 (Lembaga Pengembangan Kinerja Dosen, 2022)
This writing was conducted to examine the effect of the variables Earning Per Share (EPS), Dividend Per Share (DPS), and Return On Equity (ROE) on stock prices in mining companies listed on the Indonesian stock exchange for the 2017-2020 period. The data used in this paper were obtained from financial report data published by IDX, which was taken from the website www.idx.co.id. The population in this paper are 47 mining companies listed on the IDX. The sampling technique used was the purposive sampling technique so that there were 10 research samples. The results show that Earning Per Share, Dividend Per Share, and Return On Equity simultaneously affect stock prices in mining companies listed on the IDX for the 2017-2020 period. Partially, the Earning Per Share variable has a significant effect on the stock price of mining companies, while the Dividend Per Share and Return On Equity variables have no significant effect on the stock price of mining companies listed on the IDX for the 2014-2020 period.